Efektivitas Penerapan Sistem Informasi Akuntansi, Sistem Pengendalian Intern, Lingkungan Kerja dan Kinerja Karyawan - Juniarta, I Gede Pradana; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2023)
The research aims to determine the effect of the effectiveness of implementing accounting information systems, internal control systems, work environment on employee performance. This research was conducted at the LPD in South Kuta and Kuta Districts. The number of samples taken was 45 employees using saturated sampling technique. The analysis technique used is multiple linear regression. The results of this study indicate that the effectiveness of implementing accounting information systems has a positive effect on employee performance. The internal control system has a positive effect on employee performance. The work environment has a positive effect on employee performance. For the LPD in the sub-districts of South Kuta and Kuta, the results of this study can be used as additional information about the factors that affect employee performance, so that the performance of LPD employees in the South Kuta and Kuta sub-districts can be further improved. Keywords: Effectiveness of Accounting Information Systems; Internal Control System; Work Environment; Employee Performance